Creating Markets in Chile : A Stronger Private Sector for a More Productive and Inclusive Society - Country Private Sector Diagnostic - International Finance Corporation (Washington, DC, 2022)
Chile has long had a strong private sector that has enjoyed an accommodating and supportive policy environment. The imperative of building a green, knowledge-based, inclusive economy will inevitably continue to rely on the private sector playing a potent role as a partner in development. In an environment constrained by lower growth and productivity, Chileans are demanding access to better opportunities and improved services. The current constitutional process is an opportunity to set the stage for the private sector to be a stronger partner in building a more inclusive society and an innovative, productive, and greener economy. For this to happen, this country private sector diagnostic (CPSD) argues that three avenues will be essential: enhancing productivity, building a knowledge-based economy through more support to innovation, and upgrading skills for greater inclusion and innovation.